1991
DOI: 10.1182/blood.v77.9.2023.2023
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor tau delta +/CD3+4-8-T- cell acute lymphoblastic leukemias: a distinct subgroup of leukemias in children. A report of five cases

Abstract: In a 10-year study of T-cell acute lymphoblastic leukemias (T-ALL) in children, we have identified five cases expressing the T-cell receptor tau delta (TCR tau delta). The incidence (26%) of TCR tau delta+T-cell leukemias in our material was high. Clinically, the TCR tau delta+ leukemias represented a distinct subgroup of T-cell leukemias. Mean age at onset of disease, 1.8 years, was remarkably low for mature T-cell leukemias. White blood cell counts were high, lymph node enlargements were discrete, and no med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
6
1
Order By: Relevance
“…Few series have described the clinical course and outcome of  T-ALL [3]. A small series published in 1991 describes 5 cases of gamma-delta T ALL in children [15]. In this review the mean age at onset of the disease was 1.8 years compared to 5.9 years seen in other pediatric T-ALLs.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Few series have described the clinical course and outcome of  T-ALL [3]. A small series published in 1991 describes 5 cases of gamma-delta T ALL in children [15]. In this review the mean age at onset of the disease was 1.8 years compared to 5.9 years seen in other pediatric T-ALLs.…”
Section: Discussionmentioning
confidence: 79%
“…All patients received multiagent induction chemotherapy that [14]. Another study from Germany demonstrated that patients with poor MRD response has relatively more benefi t from allogeneic transplant in fi rst complete remission (CR) when compared to those with good MRD response [15]. However, there is paucity of this data applicable to the small subset of  T-ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found the incidence of γδ T-ALL to be~15% in childhood T-ALL, which is within the range of 10-26% reported in other studies. 9,40 The proportion of African Americans and patients with mediastinal mass was higher in the γδ T-ALL group compared to the other T-ALL group. Ethnic differences in the frequency of γδ T cells, with a higher proportion of Vδ1 T cells in healthy African Americans compared to Caucasians have been reported.…”
Section: Discussionmentioning
confidence: 95%
“…[3][4][5][6][7][8] For patients with T-cell acute lymphoblastic leukemia (T-ALL) expressing the γδ TCR, case reports have suggested that they are at higher risk for poor outcomes. 7,[9][10][11][12][13][14][15][16][17][18][19][20] Recently, identification of γδ T-cell lineage-specific genetic alterations leading to the fusion transcripts, SET-NUP214 and CALM-AF10, have been associated with chemotherapy resistance and poor prognosis, respectively, suggesting a biological link to the clinical outcome for patients with T-ALL. 19,20 For patients with T-ALL, one of the most significant prognostic indicator is the level of minimal residual disease (MRD) during and after remission induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in T‐cell malignancies have suggested that TCR expression might contribute to a biologically based understanding of clinicopathologic features and prognosis of T‐ALL patient subgroups ( Macintyre et al , 1990 ; Alfsen et al , 1991 ; Campana et al , 1993 ), and identification of T‐cell lymphoma subgroups (i.e. hepatosplenic γ/δ lymphoma) with characteristic morphologic appearance and clinical behaviour ( Jaffe, 1996).…”
mentioning
confidence: 99%